Theoretical Study of Adenine to Guanine Transition Assisted by Water and Formic Acid Using Steered Molecular Dynamic Simulations - Tolosa, Santiago; Sansón, Jorge A.; Hidalgo, Antonio (Frontiers in Chemistry, 2019)
The free energy profile of the adenine to guanine transition in the gas and aqueous phases was obtained by applying steered molecular dynamic (SMD) simulations. Three processes were considered to explain the mechanism assisted by water and formic acid molecules. The first process is hydrolytic deamination of adenine, then oxidation of the hypoxanthine previously formed, and finally, the animation from xanthine to guanine. In the gas phase these processes indicate a slow and not spontaneous conversion (ΔGg = 4.07 kcal·mol−1, k = 5.59·10−40 s−1), and a lifetime for guanine of τ = 7.75·10+22 s. The presence of solvent makes the transition more difficult by increasing the reaction energy to 26.90 kcal·mol−1 and decreasing the speed of the process to 1.63·10−55 s−1. However, it decreases the energy of the deamination process to −9.63 kcal·mol−1 and the lifetime of guanine base to τ = 6.85·10+17 s when the surrounding medium used in the transition process is aqueous. The results show that the guanine could participate in genetic mutations based on the lifetimes obtained. Transition states and intermediates structures were analyzed at the molecular dynamic level. This allows to follow the mechanism over time and to calculate thermodynamic and kinetic properties.